What is to Hand: The Fold as Landscape Within Textile Imagination. (2nd January 2023) - Thoma, Andrea
Abstract: This article explores the fold and textile imagination within art by using as main case study the author's project Imaginary Landscapes . This work consists of a series of photographs taken during the first COVID-19 lockdown in the UK in 2020 and was motivated by a longing for spaces and places at a time of confinement. It provided an opportunity to work with "material to hand", pointing to Martin Heidegger and Barbara Bolt's discussion of his theory regarding "handling." The cloth as arranged or folded allows for light to enhance form whilst suggesting landscapes such as shorelines, mountains, forests, deserts or volcanoes. The discussion refers to Gilles Deleuze's reading of Leibniz, Christine Buci-Gluckmann's observations on the Baroque, and to various theoretical and artistic positions concerning the fold, drapery, and textile imagination within different visual contexts, including Giuliana Bruno's observations on the fold in relation to the screen. Imaginary Landscapes is explored with particular attention to contemporary artists Christo and Jeanne Claude, Christian Boltanski and Angela de la Cruz. The argument concludes that the fold as visual and conceptual process allows us to engage in spatio-temporal relations where the appreciation of materiality through handling/folding informs ideas of movement within and across media.